Suporte automatizado para desenvolvimento de ontologias utilizando padrões ontológicos de domínio - Souza, André Kapich (2017)
Ontology Engineering has evolved a lot in the last decades, with a growing number of methodologies, tools and applications being proposed and tried out in academia and industry. Through ontologies, the shared knowledge of a domain can be modeled to be communicated between people and automated systems. With this, the use of ontologies becomes an important tool in several areas of knowledge to structure, organize and support the sharing of the concepts that are inherent to these areas. In addition, with the use of ontologies, interoperability between systems becomes possible, due to the standardization and the use of patterns in its construction. However, the development of ontologies from scratch is a difficult and complex task, since an ontology must provide a complete and coherent representation of a specific part of the world. Thus, reuse is highly recommended in its development, allowing the ontologies to be built based on pre-existing models, leading to better results as to their quality. In this sense, Ontological Patterns (OPs) are considered as interesting tools to facilitate reuse. Recently, several authors of the Ontology Engineering community have already proposed OPs and mechanisms to apply them. However, automated systems to support their use in practice are still rare. To fill this gap, this dissertation proposes an editor for OPs catalogues, whose objective is to support the management and reuse of these OPs. Thus, the OPs catalogue approach can be applied in the construction of ontologies, with automatic support. In the development of the proposed editor, we opted to extend an existing ontology editor (OLED) to take advantage of its modeling, verification, transformation and validation tools. Three specific OPs catalogues for the Service, ISO-based Software Process and Collaboration domains have also been partially implemented. In addition, this dissertation describes three examples of utilization, one for each of the mentioned domains, aiming to demonstrate the viability of the ontology building approach using OPs catalogues with the use of the developed editor, emphasizing also the benefit of the reuse of OPs.